The human milk endocannabinoidome is preserved by high hydrostatic pressure processing but altered by holder pasteurization - Marousez, Lucie; Dumais, Elizabeth; Tran, Léa Chantal; Dubernat, Laure; De Lamballerie, Marie; Gottrand, Frédéric; Ley, Delphine; Flamand, Nicolas; Di Marzo, Vincenzo; Lesage, Jean (Frontiers in Pediatrics, 2025)
IntroductionThe microbiological safety of donor milk (DM) is commonly ensured by holder pasteurization (HoP, 62.5°C for 30 min) in human milk banks despite its detrimental effects on several bioactive factors. We compared the concentration of twelve endocannabinoid (eCB)-like mediators in raw DM and in DM after holder pasteurization or high hydrostatic pressure processing (HHP, 350 MPa at 38°C), a non-thermal substitute for DM pasteurization.MethodsWe measured five N-acyl-ethanolamines (NAEs) and seven 2-mono-acyl-glycerols (2-MAGs) in raw-DM, HHP-DM and HoP-DM using high-performance liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS).ResultsHoP-DM and HHP-DM demonstrated comparable concentrations compared with raw DM of 2-MAGs as well as for N-docosapentaenoyl-ethanolamine (DHEA, an NAE). However, four other NAEs, including N-arachidonoyl-ethanolamine (AEA), N-palmitoyl-(PEA), N-oleoyl -ethanolamine (OEA) and N-linoleoyl-ethanolamine (LEA) were significantly increased by HoP.ConclusionOur study suggests that HHP-DM may more suitable than HoP-DM to improve the development of preterm infants through the preservation of milk eCB mediators at level close to their initial levels in raw DM.